Radiological Assessment of Pituitary Hyperplasia in Newly Diagnosed Cases of Primary Hypothyroidism after Hormone Therapy: A Longitudinal Study - Manoj Mathur; Rajesh K Badhan; Sudesh Kumari; Amit Mehta (Journal of Clinical and Diagnostic Research, 2023)
Introduction: With long-standing hypothyroidism, thyrotrophin hyperplasia can result in the enlargement of the pituitary gland. Regression of the hyperplasia has been shown to occur following adequate treatment of primary hypothyroidism with hormone replacement. Characteristics of pituitary gland hyperplasia on Magnetic Resonance Imaging (MRI) have been described previously in profound primary hyperthyroidism cases. But, hyperplasia and its regression have not been well defined in newly diagnosed acute and uncomplicated cases after thyroid hormone therapy. Aim: To assess pituitary gland size on MRI in the newly diagnosed acute cases of primary hypothyroidism after eight weeks of hormone replacement therapy. Materials and Methods: This longitudinal study was carried out by enrolling 50 patients of recently diagnosed primary hypothyroidism in the Department of Radiodiagnosis, Government Medical College and Rajindra Hospital, Patiala, India from July 2018 to June 2021. In all newly diagnosed cases of primary hypothyroidism, MRI of the pituitary gland was done and the size of the gland was measured in the coronal section before the start of treatment. MRI of all the patients was also done after treatment with levothyroxine at the interval of eight weeks to assess the size of pituitary gland. Student t-test was used for pre and post-treatment measurement. Data was entered in MS Excel and analysed using Statistical Package for Social Sciences (SPSS) software. Results: Mean age of the patients included was 36.9±14.1 years. The mean Thyroid Stimulating Hormone (TSH), Triiodothyronine (T3), Triiodothyronine (T4) levels were 27.5±71.1 miu/l, 0.72±0.33 ng/ml, and 3.6±1.4 mcg/dl, respectively. The mean size of the pituitary gland before treatment was 6.3±1.9 mm and after eight weeks of treatment was 5.5±1.9mm (p=0.97). Conclusion: This study does not find significant radiologically evident hyperplasia of pituitary gland in newly diagnosed cases of primary hypothyroidism, which might be because of MRI in the initial stage of the disease.